2010
DOI: 10.1073/pnas.0914483107
|View full text |Cite
|
Sign up to set email alerts
|

Lower number of cerebellar Purkinje neurons in psychosis is associated with reduced reelin expression

Abstract: Reelin is an extracellular matrix protein synthesized in cerebellar granule cells that plays an important role in Purkinje cell positioning during cerebellar development and in modulating adult synaptic function. In the cerebellum of schizophrenia (SZ) and bipolar (BP) disorder patients, there is a marked decrease (≈50%) of reelin expression. In this study we measured Purkinje neuron density in the Purkinje cell layer of cerebella of 13 SZ and 17 BP disorder patients from the McLean 66 Cohort Collection, Harva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 42 publications
2
69
2
Order By: Relevance
“…Interestingly, Maloku et al (2010) have also found a similar PC loss in adult reelin-haploinsufficient mice, and have interpreted their findings in the context of reelin deficiency and cerebellar abnormalities observed in schizophrenia, thus underscoring the links between reelin and psychosis. The question why reelin haploinsufficiency leads to cell loss in the male but not in the female cerebellum, and how high levels of estradiol at P5 inhibit cell loss, cannot be answered yet, but recent data indicate that PCs show a peak of apoptosis during the first postnatal week in the mouse (Jankowski et al, 2009).…”
Section: Implications For the Neurobiology Of Asdmentioning
confidence: 95%
“…Interestingly, Maloku et al (2010) have also found a similar PC loss in adult reelin-haploinsufficient mice, and have interpreted their findings in the context of reelin deficiency and cerebellar abnormalities observed in schizophrenia, thus underscoring the links between reelin and psychosis. The question why reelin haploinsufficiency leads to cell loss in the male but not in the female cerebellum, and how high levels of estradiol at P5 inhibit cell loss, cannot be answered yet, but recent data indicate that PCs show a peak of apoptosis during the first postnatal week in the mouse (Jankowski et al, 2009).…”
Section: Implications For the Neurobiology Of Asdmentioning
confidence: 95%
“…By extension, altered STS expression is likely to adversely affect the development of these structures. Hence, high levels of STS expression in the thalamus, basal ganglia and cerebellar neuroepithelium (which gives rise to GABAergic and glutamatergic neurons of the cerebellum; Hoshino et al 2005) were of particular interest, given prior data suggesting aberrant development of these regions in both ADHD (Dickstein et al 2006;Perlov et al 2009;Silk et al 2009;Valera et al 2007) and schizophrenia (Ellison-Wright & Bullmore 2010;Maloku et al 2010). Similarly, altered STS function in the hypothalamus/pituitary gland, olfactory epithelium and tongue could feasibly play a role in the altered hypothalamic-pituitary-adrenal axis responsivity (van West et al 2009), odor detection abnormalities (Karsz et al 2008;Romanos et al 2008) and tongue characteristics (Atmetlla et al 2006) previously described in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…RELN is expressed in Cajal-Retzius cells during early development and from many GABAergic cells in multiple cortical layers shortly after birth (Alcantara et al, 2006). Brain tissue from schizophrenic patients also consistently report decreased expression of the RELN gene Fatemi et al, 2000Fatemi et al, , 2001Folsom and Fatemi, 2013;Guidotti et al, 2000a;Habl et al, 2012;Impagnatiello et al, 1998;Maloku et al, 2010;Ruzicka et al, 2007), which is likely the result of altered genetic and/ or epigenetic regulation (Costa et al, 2003;Grayson et al, 2005Grayson et al, , 2006Tochigi et al, 2008;Veldic et al, 2004Veldic et al, , 2007. While the RELN deficiency observed in post-mortem tissue clearly does not impact cortical architecture to the same degree as total RELN loss during cortical development, it is likely that even a small reduction of RELN would affect synaptic integration during development and/or synaptic stability and plasticity in adulthood (Frotscher, 2010).…”
Section: Gene Effects Converge Onto Gaba System Developmentmentioning
confidence: 99%
“…In addition to being a necessary component of cortical development, RELN also has a role in stabilizing neurons and synapses throughout life (Abraham and Meyer, 2003;Frotscher, 2010;Guidotti et al, 2000b). It is expressed by GABAergic interneurons and the expression of the GAD1 and RELN genes is tightly coordinated by a common epigenetic mechanism (Costa et al, 2004;Grayson et al, 2005Grayson et al, , 2006Guidotti et al, 2000a;Impagnatiello et al, 1998;Kundakovic et al, 2009;Maloku et al, 2010;Noh et al, 2005;Pesold et al, 1999;Rodriguez et al, 2002;Ruzicka et al, 2007;Tochigi et al, 2008;Veldic et al, 2004Veldic et al, , 2007. In addition, rodent models show that RELN deficiency alone can result in downstream reductions of both GAD1 (Kutiyanawalla et al, 2012;Nullmeier et al, 2011;Pascual et al, 2004;Takayama, 1994) and BDNF (Pillai and Mahadik, 2008).…”
Section: Gene Effects Converge Onto Gaba System Developmentmentioning
confidence: 99%